The impact of smoking and alcohol consumption on fetal development: a review - Wójcik-Krowiranda, Katarzyna; Leśniczak, Beata; Bieńkiewicz, Andrzej (Nursing Problems / Problemy Pielęgniarstwa, 2026)
Abstract Cigarettes and alcohol are the most popular stimulants. In Poland, a large proportion of the population habitually smokes tobacco products. The report Health Behaviors of Pregnant Women shows that only one out of ten women quit smoking in order to expand their family. Every year in Poland, over 100,000 children are born exposed to tobacco smoke in their prenatal development. In 2021, the average per capita consumption of pure alcohol in Poland was nearly 10 liters. Fetal alcohol spectrum disorder and the full syndrome occur in 20 out of 1000 and 4 out of 1000 newborns, respectively. Pregnant women who smoke and drink alcohol are at greater risk of pregnancy-related pathologies and intrauterine growth retardation. Fetal alcohol spectrum disorder is incurable, but can be prevented by abstaining from alcohol throughout pregnancy. The World Health Organization (WHO) recommends raising awareness of the harmful effects of smoking and taking action to support women in quitting the habit.